2006
DOI: 10.4319/lo.2006.51.3.1315
|View full text |Cite
|
Sign up to set email alerts
|

In situ fluxes and zonation of microbial activity in surface sediments of the Håkon Mosby Mud Volcano

Abstract: From the Hå kon Mosby Mud Volcano (HMMV) on the southwest Barents Sea shelf, gas and fluids are expelled by active mud volcanism. We studied the mass transfer phenomena and microbial conversions in the surface layers using in situ microsensor measurements and on retrieved cores. The HMMV consists of three concentric habitats: a central area with gray mud, a surrounding area covered by white mats of big sulfide oxidizing filamentous bacteria (Beggiatoa), and a peripheral area colonized by symbiontic tube worms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
187
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 201 publications
(197 citation statements)
references
References 44 publications
8
187
2
Order By: Relevance
“…Oxygen uptake rates measured on marine Beggiatoa (trichome diameter 20 mm) in a setup similar to the one of this study showed a 10 times higher biovolume-specific oxygen consumption (32000 mmol dm À3 h À1 , LP Nielsen et al, 2006 (unpublished data)). Thus, it seems that Thioploca and Thiomargarita, which populate OMZs and which rarely experience oxygenated conditions, have a metabolic potential less optimized for the use of oxygen than large marine Beggiatoa, which thrive in sediments underlying oxygenated bottom water (for example, Mussman et al, 2003;Preisler et al, 2007;de Beer et al, 2006). Denitrification by Thioploca was not detectable, either by microelectrodes (o0.2 % of the sulphide uptake rates) or by 15 N experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen uptake rates measured on marine Beggiatoa (trichome diameter 20 mm) in a setup similar to the one of this study showed a 10 times higher biovolume-specific oxygen consumption (32000 mmol dm À3 h À1 , LP Nielsen et al, 2006 (unpublished data)). Thus, it seems that Thioploca and Thiomargarita, which populate OMZs and which rarely experience oxygenated conditions, have a metabolic potential less optimized for the use of oxygen than large marine Beggiatoa, which thrive in sediments underlying oxygenated bottom water (for example, Mussman et al, 2003;Preisler et al, 2007;de Beer et al, 2006). Denitrification by Thioploca was not detectable, either by microelectrodes (o0.2 % of the sulphide uptake rates) or by 15 N experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Sulphide oxidation by the large marine sulphur bacteria affects mineral cycling in many organic-rich surface sediments (for example, Ferdelman et al, 1997;Mussmann et al, 2003;de Beer et al, 2006;Preisler et al, 2007). Only one study has addressed the biomass-specific sulphide oxidation rate of Thioploca (Otte et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The profiler module (Wenzhö fer et al, 2000;de Beer et al, 2006) was equipped with microsensors for dissolved oxygen, temperature (Pt100, UST Umweltsensortechnik GmbH, Geschwenda, Germany), pH, H 2 S, redox and pCO 2 (Microelectrodes Ltd, Ottawa, Canada). The temperature and CO 2 minisensors had a diameter of 2 mm.…”
Section: Porewater Geochemistrymentioning
confidence: 99%
“…The white color of the gelatinous spheres is an indication for the presence of elemental sulfur, and microscopic analyses later revealed a high density of light-reflecting granules typical for the sulfur inclusions of giant sulfide-oxidizing bacteria (Teske and Nelson, 2006). The white filaments were also observed surrounding the gelatinous masses on top of the sediment and were morphologically attributed to bacteria of the genus Beggiatoa, mat-forming giant sulfide oxidizers known to occur on highly reduced sulfidic sediments (Ahmad et al, 1999;Mills et al, 2004;de Beer et al, 2006). The underlying sediment was characterized by a beige-brown top layer above a dark gray to blackish horizon.…”
Section: Resultsmentioning
confidence: 99%